Evaluating the relationship of parameters hydraulic impact device and its drive - Volkov N.N.; Redelin R.A.; Kravchenko V.A.; Kamanin Yu.N.; Andreev A.V (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2020)
The article deals with some questions about the influence of drive parameters on the characteristics of hydraulic shock devices, noted during the analysis of the results of mathematical modeling. Using mathematical modeling, numerical experiments were performed and diagrams of the characteristics of a hydraulic shock system were obtained that characterize the dynamics of its operation with various types of drive engines, such as an electric motor, an internal combustion engine, and an "ideal" engine. The parameters of the hydraulic shock device and the setting of the pressure- relive valve remained unchanged. As a result of numerical experiments obtain graphs of displacement and velocity of the piston, displacement of the control valve, pressure in the chambers of working and return stroke, the position of the piston of the accumulator, the pump flow rate in time. A comparison is given of the types of hydraulic shock devices that are currently most widely used in road construction vehicles (equivalent in power to an electric engine and an internal combustion diesel engine). Special attention is paid to the relationship between the parameters of the hydraulic shock device and its drive. The conclusions are made based on the dependencies obtained as a result of computational experiments. The studies show that there are significant influence parameters of the drive on the characteristics of hydraulic impact devices (hammers, breaker), and, accordingly, the need to consider drive parameters by designing and operating it.